Adsorption for Lead Removal by Chitosan from Shrimp Shells - Ratih Pratiwi; PS Dyah Prinajati (Universitas Trisakti, 2018)
Aim: The objective of this study is to obtain the optimum efficiency of Lead (Pb) removal by adsorption using shrimp shells chitosan. Adsorption is one of the alternative ways to treat heavy metal. Various substances can be used as adsorbents for the adsorption process. One of the natural adsorbents that can be utilized is shrimp shells. Methodology and Results: In general, the process of making chitin into chitosan includes demineralization with dilute HCl, deproteinization with dilute NaOH, then deacetylation of chitin using concentrated NaOH. This study would demonstrate the adsorption on artificial waste containing 100 mg/L of Pb using 1 gram of chitosan with variations in pH (4, 5, 6) and time (30, 60, 90 minutes) to determine the effectiveness of chitosan made of shrimp shells in reducing Pb concentration. The results show that the highest removal efficiency of lead was achieved at pH 4 and 90 minutes duration with a removal percentage of 99.88%. Conclusion, significance, and impact study: Chitosan compounds as the results of shrimp shells processing have amine groups (NH2) which are nucleophiles (rich in electrons). It is favorable to be used as biocoagulants or bioadsorbents of lead heavy metal with a removal efficiency of above 90%.